The 'Sekolah Sak Ngajine' Program; The Habit of loving the Qur'an from an Early Age based on Tilawati - Mustajab Mustajab; Fathor Rozi; Hasan Baharun; Hikmatul Maulidiya (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to describe the implementation or application of the 'Sekolah Sak Ngajine' Program as a habit of loving the Qur'an from an early age in RA Khodijah II Sebaung, Gending District. The 'Sekolah Sak Ngajine' program is taken from the Javanese language, which means School While Reciting the Qur'an. This habituation program is packaged in Qur'an learning activities using the Tilawati method. This research uses a qualitative descriptive approach with the type of case study. This study found that the 'Sekolah Sak Ngajine' program can condition the tendency of the world of children to be active and challenging to concentrate so that the quality and quantity targets can be achieved well in learning the Qur'an. Through the 'Sekolah Sak Ngajine' program, it can have a tremendous impact on students, namely instilling the habit of learning the Qur'an to students so that they can foster a sense of love for the Qur'an from an early age in RA Khodijah II Sebaung, Gending District, Probolinggo Regency. The implication is that learning the Qur'an in early childhood requires creativity, patience, and patience from teachers in teaching.